School DNA and Its Transfer - Döş, İzzet (American Journal of Human Ecology, 2013)
<!--[if gte mso 9]> <![endif]--> This study aims to examine the concept of “organizational DNA” which clarifies the features of an organization and helps to predict about the state of organizations in terms of schools and to bring “DNA transfer” up for discussion. Thus, a descriptive study was conducted with the help of six high school principals. The study was carried out by using maximum variation sampling with the phenomenological pattern. The data were collected through a questionnaire with open-ended questions, interviews and focus group discussions. Descriptive and content analysis methods were used to analyze the data. At the end of the study, four different features regarding the school DNA were defined and it was suggested that rotations, training school principals and leader teachers and replacement of administrators may be effective in transferring school DNA. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->